Antimicrobial Activity of the Ethanolic Extract of Durio zibethinus Rind against ESBL-producing Escherichia coli and Klebsiella pneumoniae : Antimicrobial Activity of the Ethanolic Extract of Durian Rind against ESBL-producing E. coli and K. pneumoniae - Kannady, Johnson; Mayasari, Evita; Mardiani, Tengku Helvi; Hutagalung, Sunna Vyatra; Alona, Ivana; Simatupang, Maria Magdalena (TALENTA Publisher, Universitas Sumatera Utara, 2025)
Background: Durio zibethinus (durian) contains secondary metabolites with antibacterial potency, such as alkaloids, flavonoids, saponins, tannins, and glycosides. Indonesia is one of the world’s largest producing countries of durian, yet the thorny part of the fruit rind often ends up as waste. Investigations of durian rind for its antimicrobial activity will maximize the benefits and prevent waste accumulation. Objective: In this experimental study, we analyzed the antimicrobial activity of ethanolic extract of durian rind against extended-spectrum beta-lactamase (ESBL)-producing Escherichia coli and K. pneumoniae in vitro. Methods: This study used a one-group posttest-only design. The disc diffusion method for antimicrobial susceptibility test was used to test the ethanolic extract of durian rind against ESBL-producing E. coli and K. pneumoniae, each with six experimental repetitions to observe the inhibition zone produced around discs containing the extracts at various concentrations (12.5%, 25%, 50%, 75%, 80%, and 100%). Results: Ethanolic extract of durian rind showed an inhibition zone against ESBL-producing E. coli at the extract concentration of 50%, with an average inhibition zone of 3.57 mm. The inhibition zone was also observed against ESBL-producing K. pneumoniae at the extract concentration of 75%, with an average inhibition zone of 3.73 mm. Conclusions: The ethanolic extract of durian rind showed inhibition zones against ESBL-producing E. coli and K. pneumoniae, showing its potential antimicrobial activity in vitro.